2019
DOI: 10.1021/acsptsci.9b00018
|View full text |Cite
|
Sign up to set email alerts
|

Encoding the β-Arrestin Trafficking Fate of Ghrelin Receptor GHSR1a: C-Tail-Independent Molecular Determinants in GPCRs

Abstract: G-protein-coupled receptors (GPCRs) can bias signaling through distinct biochemical pathways that originate from G-protein/receptor and β-arrestin/receptor complexes. Receptor conformations supporting β-arrestin engagement depend on multiple receptor determinants. Using ghrelin receptor GHR1a, we demonstrate by bioluminescence resonance energy transfer and fluorescence microscopy a critical role for its second intracellular loop 2 (ICL2) domain in stabilizing β-arrestin/ GHSR1a core interactions and determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…More precisely, substitution of the proline 148 (P148A) residue generated a GHSR1a mutant that had reduced β-arrestin affinity and was biased toward the Gα q/11 signaling. However, mutating the neighboring leucine 149 (L149G) residue selectively abolished signaling to the Gα q/11 pathway, generating a complete biased GHSR1a mutant toward the β-arrestin signaling pathway [86,87]. These findings together with spectroscopic [88] and crystal structure data [89] suggest that G protein and β-arrestin cannot simultaneously engage ICL2 residues, which supports a role for conformation-dependent signaling bias at the ghrelin receptor and makes GHSR1a an effective prototype for decoding biased agonism at GPCRs.…”
Section: Biased Ghrelin Receptorsmentioning
confidence: 86%
See 3 more Smart Citations
“…More precisely, substitution of the proline 148 (P148A) residue generated a GHSR1a mutant that had reduced β-arrestin affinity and was biased toward the Gα q/11 signaling. However, mutating the neighboring leucine 149 (L149G) residue selectively abolished signaling to the Gα q/11 pathway, generating a complete biased GHSR1a mutant toward the β-arrestin signaling pathway [86,87]. These findings together with spectroscopic [88] and crystal structure data [89] suggest that G protein and β-arrestin cannot simultaneously engage ICL2 residues, which supports a role for conformation-dependent signaling bias at the ghrelin receptor and makes GHSR1a an effective prototype for decoding biased agonism at GPCRs.…”
Section: Biased Ghrelin Receptorsmentioning
confidence: 86%
“…Besides introducing mutations that could favor activation of a specific G protein signaling over another, functionally biased ghrelin receptors that could distinguish between G protein and arrestin-mediated signaling have also been described [86,87]. A recent study demonstrated that introducing a single point mutation at the second intracellular loop (ICL2) of the ghrelin receptor was enough to produce GHSR1a mutants with opposite signaling-biased phenotypes [86]. More precisely, substitution of the proline 148 (P148A) residue generated a GHSR1a mutant that had reduced β-arrestin affinity and was biased toward the Gα q/11 signaling.…”
Section: Biased Ghrelin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…GHSR1a primarily couples to Gα q/11 , thus stimulating the production of intracellular inositol triphosphate (IP) 3. Like other GPCRs, agonist stimulation results in phosphorylation of GHSR1a by kinases, including GPCR kinase 2 (GRK2) and PKC ( 15 ), and β-arrestin recruitment. Notably, GHSR1a contains several phosphorylation sites within the C-terminal tail, some of which have been shown to be important for β-arrestin recruitment ( 16 ).…”
mentioning
confidence: 99%